5-Amino-2,4,6-triiodoisophthalic acid–4,4′-bipyridineN,N′-dioxide–water (1/1/1) - Zhang, Kou-Lin; Zhang, Jin-Bo; Ng, Seik Weng (International Union of Crystallography, 2011)
The aromatic rings of the N,N′-dioxide molecule in the title compound, C8H4NI3O4·C 10H8N2O2·H2O, are twisted by 14.0 (2)°. The -CO2H substituents of the 5-amino-2,4,6-triiodo-isophthalic acid are twisted by 83.0 (2) and 86.5 (2)° out of the plane of the aromatic ring. In the crystal, the three components are linked by O - H⋯O hydrogen bonds into a three-dimensional network. An N - H⋯O inter-action also occurs. One of the amino H atom is not involved in hydrogen bonding.